NOMOPHOBHIA, PENYAKIT MASYARAKAT MODERN - Hafni, Nurlaili Dina (Jurnal al Hikmah, 2018)
Smartphone dependence triggers the occurrence of nomophobia. A smart audience will certainly never blame his media device because one of its functions is to make it easier for people to find information. The use of smartphones should be done wisely, measured, controlled and directed so as not to have a negative psychological effect on the user. The participation of parents, teachers, lecturers, government and communities is needed to guard smartphone use especially among children, teenagers and students. Media literacy activities must be promoted in every educational institution to form a media civilization that is media literate and intelligent media. Nomophobia is defined as